2019
DOI: 10.3390/bios9040126
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Superoxide Alterations Induced by 5-Fluorouracil on HeLa Cells with a Cell-Based Biosensor

Abstract: Background: In vitro cell culture monitoring can be used as an indicator of cellular oxidative stress for the assessment of different chemotherapy agents. Methods: A cell-based bioelectric biosensor was used to detect alterations in superoxide levels in the culture medium of HeLa cervical cancer cells after treatment with the chemotherapeutic agent 5-fluorouracil (5-FU). The cytotoxic effects of 5-fluorouracil on HeLa cells were assessed by the MTT proliferation assay, whereas oxidative damage and induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
3
6
0
Order By: Relevance
“…Among these drugs, docetaxel significantly increased the expression level of caspase-3 within 8 h, which is consistent as reported previously that docetaxel exhibited strong apoptotic induction effect both on HeLa cells and MCF-7 cells (Al-Abd et al, 2011). 5-FU and adriamycin induced the activation of caspase-3 at 48 h in Hela cells, which is similar to the former studies (Brisdelli et al, 2016;Mavrikou et al, 2019). In contrast, the induction of caspase-3 activity in MCF-7 cells by adriamycin was negligible relative to that in HeLa cells, while caspase-3 in MCF-7 cells was not activated by 5-FU stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…Among these drugs, docetaxel significantly increased the expression level of caspase-3 within 8 h, which is consistent as reported previously that docetaxel exhibited strong apoptotic induction effect both on HeLa cells and MCF-7 cells (Al-Abd et al, 2011). 5-FU and adriamycin induced the activation of caspase-3 at 48 h in Hela cells, which is similar to the former studies (Brisdelli et al, 2016;Mavrikou et al, 2019). In contrast, the induction of caspase-3 activity in MCF-7 cells by adriamycin was negligible relative to that in HeLa cells, while caspase-3 in MCF-7 cells was not activated by 5-FU stimulation.…”
Section: Discussionsupporting
confidence: 92%
“…This result confirmed our anticipation of the higher level of ROS in cancer cells and tissues compared to healthy ones (25,26). Also, various groups utilized SOD-based biosensors for detecting superoxide radicals in cancer cells (27) and tissues (13,28), and reported higher levels of superoxide radicals in the cancer samples. For instance, Campanella et al (2000) has reported an approximately 15 times more intense amperometric response for cancerous renal tissue compared to healthy tissue (13).…”
Section: Clinical Application Of Gelatin-alginate-tio2-sod Biosensorsupporting
confidence: 85%
“…Viabilities lower than 20% in cancer cells were found for both systems at 72 h, at the highest and lowest dilutions. This result is consistent with previous findings where low concentrations of 5-FU induced cytotoxicity on HeLa cells 49.…”
supporting
confidence: 94%